An Analysis of Support Services for Student Athletes Attending Division I Institutions of Higher Education: A Summary - Swann, Paul R. (My University, 1989)
The purpose of this study was to identify and analyze the significant variables related to the effectiveness of support services for student athletes attending NCAA Division I institutions. For comparative purposes, the investigator sent questionnaires to all (285) Division I public and private institutions. Many of the 134 responding individuals supervised or directed support service programs for student athletes. This was an abbreviated form of the author's dissertation, which shared conclusions comparing private and public institutions. The study found little differerences between the two types in terms of offerings to students (e.g., tutoring, academic support). The recommended caseload is no more than 100 students to 1 advisor.
Keywords: academic support; Division I